Synergic Effect of Combined Therapy of Hyperbaric Oxygen and Adipose-Derived Mesenchymal Stem Cells on Improving Locomotor Recovery After Acute Traumatic Spinal Cord Injury in Rat Mainly Through Downregulating Inflammatory and Cell-Stress Signalings. (November 2022) - Yin, Tsung-Cheng; Shao, Pei-Lin; Chen, Kuan-Hung; Lin, Kun-Chen; Chiang, John Y.; Sung, Pei-Hsun; Wu, Shun-Cheng; Li, Yi-Chen; Yip, Hon-Kan; Lee, Mel S.
This study tested whether combined hyperbaric oxygen (HBO) and allogenic adipose-derived mesenchymal stem cells (ADMSCs) would be superior to either one for improving the locomotor recovery in rat after acute traumatic spinal cord injury (TSCI) in rat. Adult-male Sprague–Dawley rats were equally categorized into group 1 (sham-operated control), group 2 (TSCI), group 3 (TSCI + HBO for 1.5 h/day for 14 consecutive days after TSCI), group 4 (TSCI + ADMSCs/1.2 × 10 6 cells by intravenous injection at 3 h and days 1/2 after TSCI), and group 5 (TSCI + HBO + ADMSCs), euthanized, and spinal cord tissue was harvested by day 49 after TSCI. The protein expressions of oxidative-stress (NOX-1/NOX-2), inflammatory-signaling (TLR-4/MyD88/IL-1β/TNF-α/substance-p), cell-stress signaling (PI3K/p-AKT/p-mTOR), and the voltage-gated sodium channel (Nav1.3/1.8/1.9) biomarkers were highest in group 2, lowest in group 1, and significantly lower in group 5 than in groups 3/4 (all P <0.0001), but they did not differ between groups 3 and 4. The spinal cord damaged area, the cellular levels of inflammatory/DNA-damaged biomarkers (CD68+/GFAP+/γ-H2AX+ cells), mitogen-activated protein kinase family biomarkers (p-P38/p-JNK/p-ERK1/2), and cellular expressions of voltage-gated sodium channel (Nav.1.3, Nav.1.8, and Nav.1.9 in NF200+ cells) as well as the pain-facilitated cellular expressions (p-P38+/peripherin+ cells, p-JNK+/peripherin+ cells, p-ERK/NF200+ cells) exhibited an identical pattern of inflammation, whereas the locomotor recovery displayed an opposite pattern of inflammation among the groups (all P < 0.0001). Combined HBO-ADMSCs therapy offered additional benefits for preserving the neurological architecture and facilitated the locomotor recovery against acute TSCI.